1999
DOI: 10.1002/(sici)1521-3935(19991101)200:11<2508::aid-macp2508>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of poly(ester-urethane)s by a pure strain of micro-organisms

Abstract: SUMMARY: Poly(butylene adipate) (PBA) and poly(ethylene succinate) (PEgS) with a M -n of 2 000 were used as building blocks of poly(ester-urethane)s. Trimethylhexamethylene diisocyanate (TMDI), TMDI/2-methyl-1,5-pentanediamine (MPDA)/TMDI and 4,49-methylenediphenyl diisocyanate (MDI) were used to build diurethane units into the polymer with a final M -n of the order of 30 000. Oxygen consumption was measured during incubation of a pure strain of gram-positive non-sporulating bacteria isolated from an industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…[3][4][5][6][7] Polycaprolactone (PCL)-based materials, including polyurethanes, were extensively investigated in the early 1970s by the groups of Cooper, 8 -10 Schollenberger, [11][12][13] and Koleske, 14 -16 who focused on the structure-property relationships. The biodegradability of polyurethanes has been well documented, [17][18][19][20][21][22] and that of PCLs has been reported to depend on the molecular weight, [23][24][25] but a conclusive correlation between the morphology (crystallinity, in this case), molecular weight, and biodegradation properties has not been established yet. This article describes the morphology of poly(ester urethane)s in which the soft segment is PCL and the hard block is built by the reaction of tolylene diisocyanate (TDI) and 1,4-butanediol (BDO).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Polycaprolactone (PCL)-based materials, including polyurethanes, were extensively investigated in the early 1970s by the groups of Cooper, 8 -10 Schollenberger, [11][12][13] and Koleske, 14 -16 who focused on the structure-property relationships. The biodegradability of polyurethanes has been well documented, [17][18][19][20][21][22] and that of PCLs has been reported to depend on the molecular weight, [23][24][25] but a conclusive correlation between the morphology (crystallinity, in this case), molecular weight, and biodegradation properties has not been established yet. This article describes the morphology of poly(ester urethane)s in which the soft segment is PCL and the hard block is built by the reaction of tolylene diisocyanate (TDI) and 1,4-butanediol (BDO).…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 shows the yield of the oligomer with an M w of less than 500 by the enzymatic degradation of the adipate-type PEU (x,y,4) in anisole at 110 8C for 6 and 24 h. It was found that the degradation rate of the adipate-type PEU (x,y,4) into the cyclic oligomer increased with the number of methylene groups (y) in the diurethane moiety. That is, PEUs (2,6,4), (3,5,4) and (3,6,4) were almost completely degraded into the corresponding cyclic oligomers for 6 h; on the other hand, the degradation rate of PEUs (2,2,4), (2,3,4) and (3,2,4) were significantly lower. This is ascribed to the flexibility of the diurethane moieties in the polymer chain for incorporation of the ester moiety into the active site of the lipase CA.…”
Section: Enzymatic Degradation Of Peu (Xyz) Into Cyclic Ester-urethmentioning
confidence: 99%
“…It has been reported that certain kinds of polyurethanes containing a polyester block as a soft segment, poly(ester-urethane)s (PEU), are subject to degradation by microbes. [3][4][5] Takamoto et al reported the lipase-catalyzed degradation of PEU in organic solvent. [6] These results indicated that the introduction of ester linkages into the polymer chain may become an effective way to design a biodegradable and enzymatically recyclable polyurethane.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the enzymatically cleavable and biodegradable polyurethane may be produced by combining the low-molecular weight biodegradable hard segment of polyurethane with enzymatically hydrolyzable linkages, such as the ester and carbonate ester. It is reported that certain kinds of polyurethanes containing a polyester block as a soft segment, poly(ester-urethane)s, are subject to degradation by microbes [6][7][8] and by lipase. [9] These results indicate that the introduction of ester linkages into the polymer chain may become an effective way to design a biodegradable and enzymatically recyclable polyurethane.…”
Section: Introductionmentioning
confidence: 99%